2020
DOI: 10.21307/tp-2020-016
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Sleepiness During Long-Duration Driving: A Preliminary Study Among Indonesian Commercial Drivers

Abstract: Fatigue and sleepiness are two major factors that have been reported to contribute to road crash and accidents in Indonesia. Fatigue among commercial drivers is probably a common phenomenon, particularly during long-duration driving. This study aimed at characterizing fatigue and sleepiness during long-duration driving. Nine commercial drivers were recruited in this field study and were requested to drive a multipurpose vehicle for three trips back and forth between two major cities. Each trip was completed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A study done by Zainy et.al on Indonesian Commercial Vehicle drivers found that prolonged driving was closely associated with undue fatigue that represented a road safety risk factor [12]. Another study done by Iridiastadi et.al found that a of six hours of intermittent driving was adequate in inducing fatigue and sleepiness, despite the seemingly sufficient amount of rest break [13]. The study done by Shen et.al found that distributions of driving-distance were not different from the length-of-driving-time distributions by driver age category, gender, time-of-day, and day-of-week.…”
Section: Resultsmentioning
confidence: 99%
“…A study done by Zainy et.al on Indonesian Commercial Vehicle drivers found that prolonged driving was closely associated with undue fatigue that represented a road safety risk factor [12]. Another study done by Iridiastadi et.al found that a of six hours of intermittent driving was adequate in inducing fatigue and sleepiness, despite the seemingly sufficient amount of rest break [13]. The study done by Shen et.al found that distributions of driving-distance were not different from the length-of-driving-time distributions by driver age category, gender, time-of-day, and day-of-week.…”
Section: Resultsmentioning
confidence: 99%